(untitled) (Bangladesh Journal of Agricultural Research, 2023)
An experiment was conducted in calcareous soil at the research farm of Regional Pulses Research Station,Madaripur during 2014 and 2015 to determine the suitable dose of B for yield maximization of different varieties of mungbean (Vigna radiata L. There were 25 treatment combinations comprising five levels of boron (0, 1.0, 1.5, 2.0 and 2.5 kg ha-1) and five varietiesof mungbean (BARI Mung-2, BARI Mung-3, BARI Mung-4, BARI Mung-5 and BARI Mung-6) along with a blanket dose of N20P25K30S10Zn2 kg ha-1. The experiment was laid out in factorial randomized complete block design with three replications. Main effect of boron indicated 1.5 kg ha-1 B was superior to other doses in respect of yield, protein content and yield traits of mungbean varieties. However, the highest yield increment (31.4%) over control was achieved from 1.5 kg B ha-1. In interactions, the maximum seed yield was achieved from var. BARI Mung-6 with the application of B @ 1.5 kg ha-1. As such cultivation of mungbean var. BARI Mung-6 with the application of boron @ 1.5 kg ha-1 along with N20P25K30S10Zn2 kg ha-1 (blanket dose) could be found suitable for yield maximization of mungbean in calcareous soils of Bangladesh. Bangladesh J. Agril. Res. 47(1): 105-118, March 2022